Solar energetic particle tracks in lunar samples: A transmission electron microscope calibration and implications for lunar space weathering. (31st August 2021) - Keller, Lindsay P.; Berger, Eve L.; Zhang, Shouliang; Christoffersen, Roy
Abstract: Transmission electron microscope (TEM) imaging techniques combined with focused ion beam sample preparation were used to calibrate the solar energetic particle track production rate in lunar samples. Track density measurements by TEM as a function of depth were obtained from lunar rock 64455 that has a well‐constrained exposure age of 2 Myr giving a track production rate of 4.4 ± 0.4 × 10 4  tracks cm −2  yr −1 for a 2π exposure at 1 AU. The typical space weathering effects in mature lunar soils (both vapor‐deposited rims and solar wind‐damaged rims) accumulate in ˜10 6  yr based on the new calibration applied to track densities in individual grains. Solar wind‐damaged rim widths in anorthite and olivine follow a power law relationship with track density and achieve steady‐state widths in a few Myr. Vapor‐deposited rim widths show no correlation with exposure age suggesting that their formation is episodic with the full width of vapor‐deposited rims accumulating in a single or a few rare impact events. Solar wind‐damaged rim development was modeled using the stopping range of ions in matter code. Modeling shows that the solar wind‐damaged rims develop rapidly and approach steady‐state values in 10 5 –10 6  yr. Anorthite and olivine record similar track densities for similar exposure ages, but their structural response to solar wind irradiation differs significantly. Solar wind‐damaged rims on olivine are not amorphous in contrast to modeling and high flux laboratory experiments and a model is proposed to account for their different response to solar wind irradiation.